Radon risk assessment in a low-energy consumption school building: A dosimetric approach for effective risk management - António Curado; Jo\~ao P. Silva; Sérgio I. Lopes (Energy Reports, 2020)
A high-occupancy elementary school building recently retrofitted, with low energy consumption and no central climatization systems for heating, cooling and ventilation, located in the North region of Portugal was widely monitored to assess radon risk as a measure of indoor air quality. The experimental campaign was implemented in the spring of 2018 and during a period of one month, the radon gas concentration was continuously assessed. The main goal of the study is to evaluate the influence of variables such as the occupancy, the location of the monitored rooms and ventilation actions that were undertaken, to effectively evaluate the risk to radon exposure in a scenario of very low energy spent for heating, cooling and ventilation. The final results showed that 46% of the rooms exceeded the limit of 300 Bq.m-3 imposed by the Portuguese legislation in force. However, when considering a dosimetric approach reflecting the school building occupation profile (SBOP), by the calculation of the Indoor Annual Effective Dose (IAED), 93% of the rooms were above the occupational dose limit of 1 mSv/year, recommended by the International Commission on Radiological Protection (ICRP). Based on the results, there is evidence that the risk associated to the exposure to radon gas in indoor environments does not depend only on its concentration in the monitored room, but also on the number of occupants, period of occupancy, ventilation rate and on the location of the room in the building.
Keywords: 330; Low-energy consumption; Occupancy; Radon mitigation; Radon risk assessment; Ventilation